An all-dielectric route to negative refraction - Zhu,Shiyu (Nanyang Technological University, 2021)
In recent years, negative refraction has become a popular topic. This project focuses on the negative refraction phenomenon of all-dielectric metamaterials. The principle of achieving negative refraction in metamaterials is introduced. An array of cylindrical resonators with periodic arrangement is built. Calculations are performed using Mathematica software and simulations are tested in COMSOL software. It is demonstrated that the all-dielectric metamaterial has negative refraction property.